Preventing injuries in water polo: have we scored?. Issue 4 (27th March 2011) - Mountjoy, M; Junge, A
Abstract : Background: Injury surveillance over time is the basis for the identification of injury trends and the development of injury prevention programs. Objective: To analyse the injury trends in water polo over a 5 year period and evaluate injury prevention programs. Setting: 2004 and 2008 Olympic Games and 2009 FINA World Championships. Participants: All male and female water polo players participating in the tournaments. Methods: New onset injuries were reported by the team physicians. Main outcome measurements: Trends in injury incidence. Results: The overall injury incidence in water polo has remained constant throughout the study period (OG 2004 20.1 per 1000 player matches; OG 2008 20.1 per 1000 player matches; and FINA 2009 19.3 per 1000 player matches). However, there have been significant differences in gender related injury incidence trends. Men's injury incidence has steadily decreased over the study period from a total of 27.6/1000 player matches in 2004 to 16.2/1000 player matches in 2008 and 14.9/1000 player matches in 2009. Women's injury incidence has shown an opposite trend over the study period (2004: 3.57/1000 player matches; 2008: 28.6/1000 player matches; and 2009: 23.8/1000 player matches). Conclusion: The decrease in injury incidence in the men's game can possibly be attributed to the institution of an injury prevention program instituted in 2005 following the identification of a high incidence of head injuries and injuries caused by foul play in 2004. In contrast, the injury prevalence in women's water polo has increased over the study period. The cause of this is unknown although may be attributed an increase in aggression in the women's style of play as they try to emulate the men's game. The rising injury incidence in women's water polo and the lack of decrease in overall combined injury rates underscores the need for further injury surveillance and implementation of injury prevention programs.